PENGGUNAAN CLAY THERAPY DALAM PROGRAM BIMBINGAN UNTUK PESERTA DIDIK TINGKAT SEKOLAH DASAR - Wirastania, Aniek (JURNAL FOKUS KONSELING, 2016)
Clay therapy has a special role in the field of guidance and counseling. Clay Therapy has been widely use by counselor to overcome problems faced by children. Clay media adores children. Therefore, this media can assist counselor to overcome the problem of children who cannot express their problems. The guidance and counseling program conducted using the concept of clay therapy has a special counselee target. Clay therapy is aimed at children of 9-12 years of age. At these ages children are in the development process, so they need facilitation for their development, especially in the cognitive and affective aspects..Keywords: Clay Therapy, Guidance and Counseling Program.